Mutation of OsGIGANTEA Leads to Enhanced Tolerance to Polyethylene Glycol-Generated Osmotic Stress in Rice - Li, Shuai; Yue, Wenhao; Wang, Min; Qiu, Wenmin; Zhou, Lian; Shou, Huixia (Frontiers in Plant Science, 2016)
Water deficit is one of the most important environmental stresses limiting plant growth and crop yield. While the identification of many key factors involved in the plant water deficit response has greatly increased our knowledge about the regulation system, the mechanisms underlying dehydration tolerance in plants are still not well understood. In our current study, we investigated the roles of the key flowering time regulator, OsGIGANTEA (OsGI), in the osmotic stress tolerance in rice. Results showed that mutation of OsGI conferred tolerance to osmotic stress generated by polyethylene glycol (PEG), increased proline and sucrose contents, and accelerated stomata movement. In addition, qRT-PCR and microarray analysis revealed that the transcript abundance of some osmotic stress response genes, such as OsDREB1E, OsAP37, OsAP59, OsLIP9, OsLEA3, OsRAB16A and OsSalT, was significantly higher in osgi than in WT plants, suggesting that OsGI might be a negative regulator in the osmotic stress response in rice.